Evaluating public administration approaches towards tax non-compliance in Europe - Colin Williams (Administrative Sciences, 2020)
Those engaging in tax non-compliance have been conventionally explained as rational economic actors partaking when the benefits outweigh the costs, and thus public administrations have sought to enforce compliance using a deterrence approach which increases the risk of detection and penalties. However, many have been found to not engage in tax non-compliance when the benefits exceed the costs. The result has been the emergence of a voluntary compliance approach viewing taxpayers as social actors who engage in tax non-compliance when there is a lack of vertical trust (in governments) and horizontal trust (in others). Using a probit regression analysis of data from special Eurobarometer surveys conducted in 2007, 2013 and 2019, the finding is that although the likelihood of participating in tax non-compliance is largely not associated with the level of penalties and risk of detection, it is significantly associated with the level of vertical and horizontal trust, with participation in tax non-compliance increasing with lower vertical and horizontal trust. The implications for theory and for how public administrations tackle tax non-compliance are then discussed.
Keywords: 350; European Union; fiscal justice; informal sector; institutional theory; public policy; social actor theory; tax awareness; tax co-responsibility; tax commitment; tax evasion; tax morale; undeclared work